The use of information and communication technologies in agricultural risk management by the agricultural extension services in Malaysia - Ali, Muhammad; Man, Norsida; Abd Latif, Ismail; Muharam, Farrah Melissa; Omar, Siti Zobidah (Gültekin ÖZDEMİR, 2018)
The study was aimed to determine the existing status of extension services provided for agricultural risk management in making use of Information and Communication Technologies (ICTs). There were 360 farmers selected through multistage cluster sampling technique and data were collected from four areas of Malaysia. The results reveal that farmers could get limited information from extension staff on the use of ICTs for disaster information. Moreover, most of the farmers still could not get support from extension staff to integrate ICTs for agricultural risk management. Farmers highlighted that extension staff need training to improve their capacity. Therefore, public and private sector should initiate various training programs firstly for the extension field staff and then diffuse various management skills and techniques into farmer fields for better agricultural risk management using ICTs.